On the phylogenetic position of Carollia manu Pacheco et al., 2004 (Chiroptera: Phyllostomidae: Carolliinae) - Velazco, Paúl M. (Zootaxa, 2013)
The Neotropical bat genus Carollia (Phyllostomidae: Carolliinae) currently includes eight species. Carollia manu was described in 2004 and is distributed in montane forests in southern Peru and Bolivia. The phylogenetic affinities of C. manu have never been assessed before. Phylogenetic analyses of cytochrome b sequences of seven of the eight known species of the genus place C. manu sister to C. subrufa. The analyses also suggest hidden diversity in the genus.